2000
DOI: 10.1029/gm121p0211
|View full text |Cite
|
Sign up to set email alerts
|

Models of mantle convection incorporating plate tectonics: The Australian region since the Cretaceous

Abstract: We propose that the anomalous Cretaceous vertical motion of Australia and distinctive geochemistry and geophysics of the Australian-Antarctic Discordance (AAD) were caused by a subducted slab which migrated beneath the continent during the Cretaceous, stalled within the mantle transition zone, and is presently being drawn up by the Southeast Indian Ridge. During the Early Cretaceous the eastern interior of the Australian continent rapidly subsided, but must have later uplifted on a regional scale. Beneath the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
(62 reference statements)
3
14
0
Order By: Relevance
“…Late Cretaceous-Paleocene rifting is inferred to have led to formation of marginal basins, including opening of the Coral Sea(Figure 1). Regional uplift may be associated with rifting(Home et al 1990) or with dynamic topographic rebound related to movement over a Cretaceous subducted slab(Gurnis et al 2000). 3D sketch of the New Guinea margin in the Palaeogene(after Hall 2002)…”
supporting
confidence: 59%
See 2 more Smart Citations
“…Late Cretaceous-Paleocene rifting is inferred to have led to formation of marginal basins, including opening of the Coral Sea(Figure 1). Regional uplift may be associated with rifting(Home et al 1990) or with dynamic topographic rebound related to movement over a Cretaceous subducted slab(Gurnis et al 2000). 3D sketch of the New Guinea margin in the Palaeogene(after Hall 2002)…”
supporting
confidence: 59%
“…Alternatively, this may have been associated with dynamic topographic rebound associated with the movement of Australia over a Cretaceous subducted slab as suggested for the eastern Australia margin by Gurnis et al (2000). Widespread Paleocene and Eocene sandstones in western Irian Jaya probably resulted from the uplift and denudation of Papua New Guinea and eastern Australia.…”
Section: Late Cretaceous and Paleocenementioning
confidence: 86%
See 1 more Smart Citation
“…The opening of the Tasman Sea would have been accompanied by a major change in both the stress and thermal regimes of the region, and may have led to regional uplift of the eastern margin as the deeper convection pattern adjusted. This model can be invoked as a possible explanation of the uplift in the Eromanga Basin which is some 1,000 km from the former subduction zone at the eastern margin (Gallagher et al 1994;Russell and Gurnis 1994;Gurnis et al 1998Gurnis et al , 2000. However, the model does not explain the uplift in Tertiary times as the subduction zone in eastern Australia that was potentially close enough to affect the basins, according to the model, had drastically moved far off by then.…”
Section: Intraplate Stressesmentioning
confidence: 89%
“…We have a number of hypotheses for this anomaly. Gurnis et al (2000) have suggested that an approximately north-south seismic anomaly beneath the Australian-Antarctic Discordance south of Australia may be the result of a slab in the mantle subducted east of Australia during the Cretaceous and subsequently overridden by Australia as it has moved east. Our anomaly 8 is at a similar depth and along strike from the Gurnis et al (2000) Australian-Antarctic Discordance anomaly and may have the same explanation if this subduction zone had continued north with a similar orientation.…”
Section: Older Subduction Systemsmentioning
confidence: 99%